2008
DOI: 10.1038/cdd.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of anoikis: reactive oxygen species as essential mediators of cell survival

Abstract: Proper attachment to the extracellular matrix (ECM) is essential for cell survival. The loss of integrin-mediated cell-ECM contact results in an apoptotic process termed anoikis. However, mechanisms involved in regulation of cell survival are poorly understood and mediators responsible for anoikis have not been well characterized. Here, we demonstrate that reactive oxygen species (ROS) produced through the involvement of the small GTPase Rac-1 upon integrin engagement exert a mandatory role in transducing a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 40 publications
(60 reference statements)
6
115
0
Order By: Relevance
“…Hence, due to their high mobility, mesenchymal cells are usually more resistant to anoikis [46,47]. In addition, professionally non-adherent cells, such as haematopoietic mature cells and leukocytes, are protected from anoikis [48].…”
Section: Physiological Protection From Anoikismentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, due to their high mobility, mesenchymal cells are usually more resistant to anoikis [46,47]. In addition, professionally non-adherent cells, such as haematopoietic mature cells and leukocytes, are protected from anoikis [48].…”
Section: Physiological Protection From Anoikismentioning
confidence: 99%
“…Indeed, ROS are key molecules that elicit pro-survival signals. Giannoni et al [48] observed that in cancer cells the oxidative intracellular milieu strongly correlates with induction of anoikis resistance; ROS production protects tumour cells from anoikis through the oxidation/activation of the tyrosine kinase Src, thus granting the activation of pro-survival pathways through a Src-dependent and ligand-independent phosphorylation of EGFR, which leads to Bim degradation. Furthermore, in human lung adenocarcinoma cells, Src activation compensates for the loss of cell-survival signals caused by disruption of cell-ECM interactions and contributes to anoikis resistance [92].…”
Section: Taddei Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are responsible for direct oxidation of the tyrosine kinase Src, thereby leading to its activation. The activated kinase in turn elicits a ligand-independent trans-phosphorylation of EGFR, that sequentially switches both ERK and Akt pathways, culminating in Bim degradation (Giannoni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of FAK by protein tyrosine kinase 6 (PTK6) also acts as an important mechanism in AI proliferation (Zheng et al, 2012). The ROS, which is constitutively high in metastatic cells, activates Src and further phosphorylates EGFR, subsequently leading to the phosphorylation of Akt and Erk, and finally, promoting the survival of cancer cells when losing ECM contact (Giannoni et al, 2008;Kim et al, 2012). The aforementioned researches suggest that the oncogenic regulations majorly positively contribute to the resistance of anoikis.…”
Section: Anoikis Related Signaling Pathways In Solid Tumorsmentioning
confidence: 99%